The selection of the types of shoes and its impact on the skin of the feet - Khalid Al Aboud (Our Dermatology Online, 2012)
The shoes are important for the skin of our feet. It is protecting feet from injurious things in the ground. Some of the dermatoses of the feet are greatly affected by the type of the shoes a patient is wearing. However, little attention is made on the value and functions of the shoes and its impact on our skin. This manuscript provides some details on this topic.